Lucio Saffaro, my personal visual memories (TEST XY. Critical review of studies on the representation of architecture and use of the image in science and art, 2017)
I first met Lucio Saffaro in 1978, after receiving a letter from Donald Coxeter, a friend, a famous mathematician from Toronto, who suggested to M.C. Escher to make the series of engravings Circle Limits on non Euclidean geometry. Coxeter wrote to me that he received a letter from a person, called Lucio Saffaro, who sent him one of his technical papers published in an Italian Encyclopedia, and he suggested that I contact him. I was producing my first film Platonic Solids and M.C. Escher with Donald Coxeter and Sir Roger Penrose. I will write on how I met and be- came friend with Lucio, using what I remember, which mathematics and which images we used to make exhibitions, films, congresses, books together. After writing many papers about his work as artist and mathematician, I would like to write a more personal but always visual approach to Lucio. In doing so, I will partially focus on the importance of mathematical models in modern and contemporary art